Signal‐to‐noise ratio estimation using adaptive tuning on the piecewise cubic Hermite interpolation model for images. Issue 6 (30th November 2015) - Sim, K. S.; Yeap, Z. X.; Tso, C. P.
Summary: An improvement to the existing technique of quantifying signal‐to‐noise ratio (SNR) of scanning electron microscope (SEM) images using piecewise cubic Hermite interpolation (PCHIP) technique is proposed. The new technique uses an adaptive tuning onto the PCHIP, and is thus named as ATPCHIP. To test its accuracy, 70 images are corrupted with noise and their autocorrelation functions are then plotted. The ATPCHIP technique is applied to estimate the uncorrupted noise‐free zero offset point from a corrupted image. Three existing methods, the nearest neighborhood, first order interpolation and original PCHIP, are used to compare with the performance of the proposed ATPCHIP method, with respect to their calculated SNR values. Results show that ATPCHIP is an accurate and reliable method to estimate SNR values from SEM images. SCANNING 38:502–514, 2016. © 2015 Wiley Periodicals, Inc.